Evolution of flow modulation from trabeculectomy to minimally invasive bleb surgery: a narrative review - Rho, Seungsoo; Han, Jong Chul; Lee, Chang Kyu (Annals of Eye Science, 2026)
Background and Objective: Trabeculectomy remains the reference standard for achieving low intraocular pressure (IOP) in glaucoma surgery but is associated with substantial postoperative management and complication risks. Although minimally invasive glaucoma surgery (MIGS) has broadened surgical options, many MIGS procedures fail to achieve IOP reduction comparable to conventional filtering surgery. More recently, subconjunctival and bleb-forming procedures, often described as minimally invasive bleb surgery (MIBS), have emerged with the aim of balancing efficacy, safety, and procedural standardization. The objective of this review is to examine the conceptual evolution of glaucoma shunt surgery and to delineate the positioning of MIBS within the spectrum of contemporary glaucoma surgical strategies, with particular emphasis on the convergence between traditional filtering surgery and minimally invasive approaches.Methods: A literature search was performed using PubMed, Embase, and the Cochrane Library for English-language articles published prior to January 2025. Search terms included “trabeculectomy”, “glaucoma drainage device”, “MIGS”, “minimally invasive bleb surgery”, “XEN”, “PreserFlo”, and “subconjunctival microshunt”. Relevant clinical studies, reviews, and landmark trials were reviewed. As this was a narrative review, no formal systematic review or meta-analysis was conducted.Key Content and Findings: Traditional filtering surgeries provide robust IOP reduction but are constrained by bleb-related morbidity, unpredictable wound healing, and high postoperative resource utilization. In contrast, conventional MIGS offers favorable safety profiles but generally achieves modest IOP lowering, limiting applicability in advanced disease. MIBS procedures seek to combine the efficacy of subconjunctival filtration with standardized implantation techniques, reduced conjunctival disruption, and potentially more predictable postoperative management. Current evidence suggests that MIBS occupies an intermediate position between MIGS and trabeculectomy, serving as a complementary option rather than a replacement. Surgical decision-making should therefore be individualized, considering disease severity, target IOP requirements, conjunctival status, patient age, and tolerance for postoperative interventions.Conclusions: MIBS represents an important advancement in flow-modulating glaucoma surgery, offering improved safety and procedural reproducibility. However, available data indicate that its pressure-lowering efficacy and long-term durability may remain inferior to conventional filtering procedures in selected cases, emphasizing its complementary role within the broader surgical spectrum.